GIS-based River Discharge Modelling - Akbari, Abolghasem (2016)
We are happy to announce that the Institute of Ocean and Earth Sciences (IOES), University of Malaya will be organizing GIS-based River Discharge Modelling Workshop. The workshop is scheduled to be held on 1 – 3 June 2016 at the University of Malaya. River discharge modelling is important part of hydrological process. It became more important when peak river discharge play as a key element and design criteria for rural and urban infrastructure and other developments. By fast growing of computer software and earth observation industries, it is highly motivated to teach the recent advances in integration of this tools for better understanding of the process and providing convenience results. This workshop aimed to demonstrate river discharge modelling using GIS-base hydrological model incorporating with public domain remote sensing data. It will also explore the main component of the GIS and required tools for river basin delineation and characterization.